Scientistsʼ Warning on Climate Change and Medicinal Plants - Applequist, Wendy L.; Brinckmann, Josef A.; Cunningham, Anthony B.; Hart, Robbie E.; Heinrich, Michael; Katerere, David R.; van Andel, Tinde (Planta Medica, 2020)
The recent publication of a World Scientistsʼ Warning to Humanity highlighted the fact that climate change, absent strenuous mitigation or adaptation efforts, will have profound negative effects for humanity and other species, affecting numerous aspects of life. In this paper, we call attention to one of these aspects, the effects of climate change on medicinal plants. These plants provide many benefits for human health, particularly in communities where Western medicine is unavailable. As for other species, their populations may be threatened by changing temperature and precipitation regimes, disruption of commensal relationships, and increases in pests and pathogens, combined with anthropogenic habitat fragmentation that impedes migration. Additionally, medicinal species are often harvested unsustainably, and this combination of pressures may push many populations to extinction. A second issue is that some species may respond to increased environmental stresses not only with declines in biomass production but with changes in chemical content, potentially affecting quality or even safety of medicinal products. We therefore recommend actions including conservation and local cultivation of valued plants, sustainability training for harvesters and certification of commercial material, preservation of traditional knowledge, and programs to monitor raw material quality in addition to, of course, efforts to mitigate climate change.
Keywords: climate change; ethnobotany; medicinal plants; sustainability; traditional knowledge; traditional medicine